Aerosol composition and sources in the central Arctic Ocean during ASCOS - R. Y.-W. Chang; C. Leck; M. Graus; M. Müller; J. Paatero; J. F. Burkhart; A. Stohl; L. H. Orr; K. Hayden; S.-M. Li; A. Hansel; M. Tjernström; et al. (Atmospheric Chemistry and Physics, 2011)
Measurements of submicron aerosol chemical composition were made over the central Arctic Ocean from 5 August to 8 September 2008 as a part of the Arctic Summer Cloud Ocean Study (ASCOS) using an aerosol mass spectrometer (AMS). The median levels of sulphate and organics for the entire study were 0.051 and 0.055 μ g m −3 , respectively. Positive matrix factorisation was performed on the entire mass spectral time series and this enabled marine biogenic and continental sources of particles to be separated. These factors accounted for 33% and 36% of the sampled ambient aerosol mass, respectively, and they were both predominantly composed of sulphate, with 47% of the sulphate apportioned to marine biogenic sources and 48% to continental sources, by mass. Within the marine biogenic factor, the ratio of methane sulphonate to sulphate was 0.25 ± 0.02, consistent with values reported in the literature. The organic component of the continental factor was more oxidised than that of the marine biogenic factor, suggesting that it had a longer photochemical lifetime than the organics in the marine biogenic factor. The remaining ambient aerosol mass was apportioned to an organic-rich factor that could have arisen from a combination of marine and continental sources. In particular, given that the factor does not correlate with common tracers of continental influence, we cannot rule out that the organic factor arises from a primary marine source.